2009
DOI: 10.1016/j.juro.2009.01.097
|View full text |Cite
|
Sign up to set email alerts
|

Losartan Preserves Erectile Function After Bilateral Cavernous Nerve Injury via Antifibrotic Mechanisms in Male Rats

Abstract: These data suggest that fibrotic activators in the penis may cause decreased erectile function after bilateral cavernous nerve injury. Angiotensin II type 1 receptor antagonism may counteract this effect and promote erectile function preservation for conditions associated with penile fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 19 publications
3
37
0
Order By: Relevance
“…Activation of Smad- and non-Smad-dependent TGF-β1 signaling pathways is believed to contribute to Ang II-induced apoptosis and tissue fibrosis [14, 15, 40, 43, 44]. It was previously reported that treatment with losartan suppressed the TGF-β1/Smad pathway and preserved erectile function [7, 21]. However, these results did not predict whether Ang II antagonism would attenuate apoptosis and fibrosis in the corpus cavernosum and severe CVOD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of Smad- and non-Smad-dependent TGF-β1 signaling pathways is believed to contribute to Ang II-induced apoptosis and tissue fibrosis [14, 15, 40, 43, 44]. It was previously reported that treatment with losartan suppressed the TGF-β1/Smad pathway and preserved erectile function [7, 21]. However, these results did not predict whether Ang II antagonism would attenuate apoptosis and fibrosis in the corpus cavernosum and severe CVOD.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a recent study revealed that decreased erectile function was accompanied by TGF-β1/Smad pathway activation in the rat corpus cavernosum following bilateral cavernous nerve injury. Treatment with losartan, an antagonist of the Ang II type 1 receptor, suppressed the TGF-β1/Smad pathway and preserved erectile function, suggesting that Ang II type 1 receptor antagonism may counteract structural changes in the corpus cavernosum and preserve erectile function [21]. In addition, recent evidence indicates that blocking of Ang II is more important than inhibition of TGF-β in non-penile tissue fibrosis [22], and combined therapy with sildenafil and losartan presented a better outcome in terms of functional and structural modification in the cavernous tissue of spontaneously hypertensive rats (SHR) as compared with either of the two drugs alone [23].…”
Section: Introductionmentioning
confidence: 99%
“…The same has been observed for hypertensive patients treated with valsartan; reduced ED and improved orgasmic function and sexual satisfaction (92). Also, it was found that losartan helps preserve erectile function in male rats after bilateral cavernous nerve injury by counter-acting fibrotic activator factors (93). However, recent study showed no change in ED progression in humans with ACEI or angioten-receptor blocker (ARB) therapy (94).…”
Section: Hypertension and Edmentioning
confidence: 76%
“…The renin-angiotensin system (RAS) has an important role in the ED regarding the remodelling process (27). Angiotensin II, an active product of the RAS, induces various physiological action, vasoconstriction, and endothelial dysfunction via the increased production of reactive oxygen species (ROS) and eicosanoids (9). Angiotensin II contributes to the vascular remodeling in the penis, resulting in the hypertension-related ED.…”
mentioning
confidence: 99%
“…Also, hypertrophy of corpus cavernous smooth muscle and vascular smooth muscle has been confirmed in the SHR (32). In previous studies, the protective effect of ARB, such as losartan and candesartan, was already investigated in the penis in the SHR (9,25). Olmesartan medoxomil (olmesartan) is a newer ARB than losartan, and more effective to antagonize the AT1R (2).…”
mentioning
confidence: 99%